PENGARUH PEMBELAJARAN KOOPERATIF DAN KEAKTIFAN SISWA TERHADAP PRESTASI BELAJAR - Reni Kusniawati (UNIB Press, 2022)
This research aims to describe (1) differences is learning achievement between students who learn with cooperative learning model type TGT with cooperative learning model type TaI. (2) differences in students achievement between those who have hig activity and students who have low activeness. (3) the influence of the interaction between learning models and student activeness on learning achievement. The desaign used in this study was the experimental squasi with a 2 x 2 factorial design. The population of the studi was all students of the grade XI MIPA SMA Negeri 1 Kota Agung Kabupaten Lahat year lesson 2020/2021. The sample selection is done by purposive random sampling teachique. Data were collected by learning achievement tests in the form of multiple choices and quistionnaives for learning activeness. The collected data was processrd statistically using a two – way variance (anava) analysis teachnique using a significance level of 0,05. The results showed that (1) the learning achievement of students who learn with the TGTtype of learning model is higher than the TAI type of learning model (2) students who have hihg activeness, their economics learning achievement is higher than students who have low avtivity. (3) there is no interaction between learning models and student avtiveness on economic learning achievement